A novel YGGT family protein is localized in the apicoplast and is essential for the organelle inheritance - Su, Wenqiang; Gu, Haorong; Zheng, Jun; Jia, Honglin (Frontiers in Cellular and Infection Microbiology, 2025)
Toxoplasma gondii is an obligate intracellular apicomplexan parasite. Most apicomplexan parasites contain an endosymbiont-derived organelle called the apicoplast. This organelle is critical for the survival of parasites because it plays a role in several essential metabolic pathways. However, the molecular mechanisms involved in maintaining the apicoplast have not been well understood. In this study, we investigated the function of an apicoplast-residing protein called TgYCAP in the inheritance of the apicoplast. Our results showed that conditional knockdown of TgYCAP severely inhibited the growth of the parasite and disrupted the inheritance of the apicoplast. In addition, the YGGT domain is essential for its function in the apicoplast.